Phyllodes tumors with and without fibroadenoma-like areas display distinct genomic features and may evolve through distinct pathways. (December 2017) - Pareja, Fresia; Geyer, Felipe; Kumar, Rahul; Selenica, Pier; Piscuoglio, Salvatore; Ng, Charlotte; Burke, Kathleen; Edelweiss, Marcia; Murray, Melissa P.; Brogi, Edi; Weigelt, Britta; Reis-Filho, Jorge
Abstract Breast fibroepithelial lesions (fibroadenomas and phyllodes tumors) are underpinned by recurrentMED12 exon 2 mutations, which are more common in fibroadenomas and benign phyllodes tumors.TERT promoter hotspot mutations have been documented in phyllodes tumors, and found to be more frequent in borderline and malignant lesions. Several lines of evidence suggest that a subset of phyllodes tumors might arise from fibroadenomas. Here we sought to investigate the genetic differences between phyllodes tumors with fibroadenoma-like areas vs. those without. We retrieved data for 16 borderline/ malignant phyllodes tumors, including seven phyllodes tumors with fibroadenoma-like areas and nine phyllodes tumors without fibroadenoma-like areas, which had been previously subjected to targeted capture massively parallel sequencing. WhilstMED12 exon 2 mutations were significantly more frequent in tumors with fibroadenoma-like areas (71 vs. 11%), an enrichment in genetic alterations targetingbona fide cancer genes was found in those without fibroadenoma-like areas, in particular inEGFR mutations and amplifications (78 vs. 14%). No significant difference in the frequency ofTERT genetic alterations was observed (71% in cases with fibroadenoma-like areas vs 56% in those without fibroadenoma-like areas). Our data suggest that the development of phyllodes tumors might follow two different evolutionary pathways: aMED12 -mutant pathway that involves the progression from a fibroadenoma to a malignant phyllodes tumor; and aMED12 -wild-type pathway, where malignant phyllodes tumors arise de novo through the acquisition of genetic alterations targeting cancer genes. Additional studies are warranted to confirm our observations and define whether the outcome differs between both pathways. Genetics: Two paths to malignant fibroepithelial breast tumors Malignant fibroepithelial breast tumors may arise by two distinct pathways: one from progression of benign tumors, and another where normal cells acquire mutations in cancer genes that result directly in the development of a more aggresive lesion. Phyllodes tumors (PTs) are rare breast tumors that start in the connective tissue; most are benign, but they are sometimes malignant. Jorge Reis-Filho from the Memorial Sloan Kettering Cancer Center in New York City, USA, and colleagues compared genetic differences between malignant PTs that resemble a benign tumor, known as fibroadenoma, and those that don't. They found that PTs with fibroadenoma-like areas were more likely to harbor mutations in exon 2 ofMED12, a gene often altered in benign breast fibroepithelial tumors, whereas PTs without fibroadenoma-like areas more commonly had mutations inEGFR and other known cancer genes. The findings suggest that some PTs arise from fibroadenomas, while others originate anew.